Indonesian EFL Students' Production of English Lexical Collocation in Writing - Jonathan Tanihardjo (Universitas Bunda Mulia, 2018)
Knowing a word is not only knowing its form and meaning. Hanks (1987) affirmed that words do not co-occur freely and randomly. Uncommon production of collocation may pose confusion to the listeners. Although a word can possibly be synonymous with one another; improper combinations of words can cause incongruity. The respondents of the study are students of the English Language and Culture Department (BBI) from semester 6 at Bunda Mulia University, as they all have accomplished their reading subjects and are expected to have a wide vocabulary at this level. This research is conducted to spot collocational errors, as well as to relate the errors to the influence of the L1 (mother tongue) in the production of the collocations in the students’ writings. From 20 students’ essays of which topic was “How do movies or televisions influence people’s behavior”, it is found that there are twenty two errors that were possibly resulted from six different causes. Keywords: Collocational errors, mother tongue